2021
DOI: 10.3390/ijms222011125
|View full text |Cite
|
Sign up to set email alerts
|

DRP1-Mediated Mitochondrial Fission Regulates Lung Epithelial Response to Allergen

Abstract: Mitochondria regulate a myriad of cellular functions. Dysregulation of mitochondrial control within airway epithelial cells has been implicated in the pro-inflammatory response to allergens in asthma patients. Because of their multifaceted nature, mitochondrial structure must be tightly regulated through fission and fusion. Dynamin Related Protein 1 (DRP1) is a key driver of mitochondrial fission. During allergic asthma, airway epithelial mitochondria appear smaller and structurally altered. The role of DRP1-m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 75 publications
1
6
0
Order By: Relevance
“…The role of Miro1-mediated mitochondrial trafficking upon exposure to a complex allergen in airway epithelial cells, and their associated inflammatory responses, had not been demonstrated in previous literature. Our results provide compelling evidence for the role of Miro1 in airway epithelial cells by mediating inflammatory responses associated with HDM exposure and build upon our previous studies showing the importance of mitochondrial DRP1 to this process ( 23 ). However, the mechanistic details underlying the observed phenotype remain unclear, including additional aspects of Miro1 biology ( 54 , 55 ) that where next explored in this study.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The role of Miro1-mediated mitochondrial trafficking upon exposure to a complex allergen in airway epithelial cells, and their associated inflammatory responses, had not been demonstrated in previous literature. Our results provide compelling evidence for the role of Miro1 in airway epithelial cells by mediating inflammatory responses associated with HDM exposure and build upon our previous studies showing the importance of mitochondrial DRP1 to this process ( 23 ). However, the mechanistic details underlying the observed phenotype remain unclear, including additional aspects of Miro1 biology ( 54 , 55 ) that where next explored in this study.…”
Section: Discussionsupporting
confidence: 86%
“…More specifically, IL-6 and IL-33, two pro-inflammatory cytokines produced by airway epithelia known to play key roles in severity of asthma inflammation ( 20 , 21 ), were modestly yet significantly upregulated in HDM-exposed mice following Miro1 deletion in club cells when compared to Ctrl HDM-challenged mice ( Figures 3A,B ). Further, the chemokine CCL20, produced by airway epithelial cells and known to play a significant role in mucus metaplasia, eosinophil recruitment, and IgE production in response to allergen ( 22 , 23 ), was also significantly upregulated in HDM-exposed Miro1 -deleted mice compared to Ctrls . ( Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,15 Upon activation by endogenous or exogenous stimulation, Drp1 accumulates in the mitochondrial outer membrane, leading to mitochondrial fragmentation and further ROS generation. 16,17 Emerging evidence suggests that overactivation of Drp1 and mitochondrial fragmentation may play a role in progression of allergic diseases, [18][19][20] perturbing the normal functions of T cells, mast cells, and NK cells. 18,21 ROS derived from mitochondrial disfunction have been proposed to promote Th2 polarization, impaired the IFN-γ expression, and heightened allergic responses through activation of JAKs and STAT6.…”
Section: Introductionmentioning
confidence: 99%
“…Their results suggested that being associated with a thicker reticular basement membrane, the pro-fibrotic profile in the airway epithelial cell transcriptome might contribute to asthma airway remodeling. In a methodologically robust study, Bruno and colleagues [4] demonstrated the importance of dynamin related protein 1-mediated mitochondrial fission for regulation of the pro-inflammatory response by respiratory epithelium and airway epithelial cell survival after exposure to house dust mites. Richards and co-workers [5] showed that short-chain fatty acids, fermentation metabolites from the gut microbiome, contributed to the recovery of barrier properties of airway epithelial cells, which might be mediated by increasing the expression of zonula occludens-1, a tight junction protein contributing to the integrity of the epithelium.…”
mentioning
confidence: 99%